Movement of biological systems on different environments - Leguizamón, C.A. (1979)
This paper describes the movement of biological systems on different kinds of environments, which was simulated with the aid of a digital computer plotter. The biological system is represented by two areas Aa and Ad, called the feeding and discard areas respectively, and separated by a constant distance d. Each triplet (Aa,Ad,d) determines the position of M with respect to E, and the consecutive positions determine the movement of the biological system. The possible movements of the biological system vary according to the areas, the spaces to be covered, the rules that govern the succession of states, etc. The plotter makes it possible to visualize these motions, so that many different interactions between M and E may be studied. It also becomes possible to determine other important parameters, such as the general direction taken by the system M, the width of its path, the distance between successive states, the possibility of environmental regeneration, etc. Therefore, this line of work contributes not only to theoretical biomathematics, but also to a wide variety of practical applications. © 1979.